Aesthetic pleasures and gendered tech-work in the 21st-century smart home. Issue 1 (February 2018) - Strengers, Yolande; Nicholls, Larissa
This article analyses visions of everyday life embedded in the 21st-century smart home, specifically the promoted aspiration to generate escalated aesthetic pleasures or 'pleasance', attained through automated and connected devices. We explore the likely outcomes and effects of this vision, drawing on our international content analysis of magazine and online articles and semi-structured interview and tours with households who live in smart homes or use automated technologies. Like the industrial revolution of the home, which arguably created 'more work for mother' by increasing cleanliness expectations, we show how the smart home is generating new forms of household work and play. These include researching, upgrading, updating, maintaining and integrating smart home technologies and programming pleasance 'scenes' for lighting, security and entertainment. We find that most of this household labour (and leisure) is being performed by men, possibly leading to more work for father .